KUALITAS PELAYANAN DI KANTOR DINAS PENANAMAN MODAL DAN PELAYANAN TERPADU SATU PINTU KOTA PALU - Novitasari Novitasari; Aulia Farida; Jery Devano; Fikra Fikra; Hj Mustainah; Intam Kurnia; Dandan Haryono (JURNAL MULTIDISIPLIN ILMU AKADEMIK, 2025)
Public service is a service activity carried out by public service providers as an effort to meet public needs and implement the provisions of laws and regulations that make the Palu City Government make public services an important mission in improving the rights of the people of Palu City in accordance with the vision of the city of Palu, namely realizing and determined to improve quality, effectiveness, efficiency, accountability and transparency of public services as mandated by Law Number 25 of 2009 concerning Public Services through the Investment Office and One-Stop Integrated Services. However, the services provided by DMPMTSP Palu City are still not satisfactory enough and this greatly affects the quality of service at DPMPTSP Palu City whether it is said to be good or not. The purpose of the study is to determine the quality of business licensing services and describe the inhibiting factors and efforts made in improving the quality of services at the Investment Office and One-Stop Integrated Services in Palu City, Central Sulawesi Province.